Casimir effect in Snyder space - Franchino-Viñas, Sebastián; Mignemi, Salvatore (Nuclear physics. B, Particle physics, 2020)
We show that two indistinguishable aspects of the divergences occurring in the Casimir effect, namely the divergence of the energy of the higher modes and the non-compactness of the momentum space, get disentangled in a given noncommutative setup. To this end, we consider a scalar field between two parallel plates in an anti-Snyder space. Additionally, the large mass decay in this noncommutative setup is not necessarily exponential.